Brain region-specific genome-wide deoxyribonucleic acid methylation analysis in patients with Alzheimer’s disease - Ren, Gang; Song, Shan; Zhang, Sheng-Xiao; Liu, Yan; Lv, Yan; Wang, Yan-Hong; Zhao, Rong; Li, Xin-Yi (Frontiers in Molecular Neuroscience, 2023)
Objective Alzheimer’s disease (AD) is a neurodegenerative disease characterized by neuropathology and cognitive decline and associated with age. The comprehensive deoxyribonucleic acid methylation (DNAm)-transcriptome profile association analysis conducted in this study aimed to establish whole-genome DNAm profiles and explore DNAm-related genes and their potential functions. More appropriate biomarkers were expected to be identified in terms of AD. Materials and methods Illumina 450KGSE59685 dataset AD (n = 54) and HC (n = 21) and ribonucleic-acid-sequencing data GSE118553 dataset AD patients (n = 21) and HCs (n = 13) were obtained from the gene expression omnibus database before a comprehensive DNAm-transcriptome profile association analysis, and we performed functional enrichment analysis by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses (KEGG). Three transgenic mice and three wild-type mice were used to validate the hub genes. Results A total of 18,104 DNAm sites in healthy controls (n = 21) and AD patients (n = 54) were surveyed across three brain regions (superior temporal gyrus, entorhinal cortex, and dorsolateral prefrontal cortex). With the addition of the transcriptome analysis, eight hypomethylated-related highly expressed genes and 61 hypermethylated-related lowly expressed genes were identified. Based on 69 shared differentially methylated genes (DMGs), the function enrichment analysis indicated Guanosine triphosphate enzymes (GTPase) regulator activity, a synaptic vesicle cycle, and tight junction functioning. Following this, mice-based models of AD were constructed, and five hub DMGs were verified, which represented a powerful, disease-specific DNAm signature for AD. Conclusion The results revealed that the cross-brain region DNAm was altered in those with AD. The alterations in DNAm affected the target gene expression and participated in the key biological processes of AD. The study provides a valuable epigenetic resource for identifying DNAm-based diagnostic biomarkers, developing effective drugs, and studying AD pathogenesis.